Patients and nursing staff views of using the education needs assessment tool in rheumatology clinics: a qualitative study. Issue 7 (24th November 2014) - Hardware, Bernadette; Johnson, Dawn; Hale, Claire; Ndosi, Mwidimi; Adebajo, Adewale
Abstract : Aims and objectives: To evaluate the usability of the educational needs assessment tool in clinical practice, from a practitioner and patient perspective and to establish whether patients perceive that they are getting an equally good or equally inadequate education service for their needs. Background: The educational needs assessment tool was developed to enable patients with Rheumatoid Arthritis to assess their education needs prior to a consultation with a health professional. The educational needs assessment tool has been translated into nine languages and measurement properties have been established, however, its usability in clinical practice has not been studied. Design: A qualitative study embedded into a multicentre RCT in which patients had been randomised into either educational needs assessment tool‐focused education (Experimental Group) or usual care (control group). Methods: Both groups were seen by a clinical nurse specialist. Sixteen patients and four clinical nurse specialists were recruited from the Rheumatology Outpatient Departments of three Acute Hospitals within the U K. Data were collected by interviews with patients and clinical nurse specialist. Analysis followed the Framework approach. Results: Patients and clinical nurse specialist found completion of the educational needs assessment tool straightforward, comprehensive and easy to use. Completing the educational needs assessment tool helped patients to focus on what they needed to know from the clinical nurse specialist. Patients in both the control group and the experimental group felt supported and reassured by their clinical nurse specialist and perceived that they received a good and adequate education provision. Conclusion: This study provides useful insights into the ability of the educational needs assessment tool to assess the educational needs of patients with rheumatoid arthritis in routine clinical practice. Relevance to clinical practice: The educational needs assessment tool would be useful as a structured guide for nurses when assessing and meeting individual patient educational needs. This has the potential to improve patient‐centred care, involve patients more actively in their care and enhance the long‐term effects of patient education provision.